Investigating the Potential Antagonistic Effect of Babaco Mosaic Virus Against Papaya Ringspot Virus in Carica papaya - Juan F. Cornejo-Franco; Omar Ruiz-Barzola; Diego F. Quito-Avila (PhytoFrontiers, 2023)
The potential antagonistic effect of babaco mosaic virus (BabMV) against papaya ringspot virus (PRSV) was investigated under greenhouse and field conditions. Carica papaya plants previously inoculated with BabMV were challenged with PRSV and monitored over time. Reverse-transcription quantitative PCR showed an average 61% reduction of PRSV genomic RNA in BabMV-PRSV-infected plants compared with singly infected plants. However, there was no antagonistic effect in the phenotypic response to PRSV, as leaf symptoms associated with PRSV were not different in mixed infections of BabMV-PRSV compared with PRSV singly infected plants. Similar results were observed in the field, where PRSV was detected in 47.1% of plants previously inoculated with BabMV and showed severe leaf symptoms. Our findings show that BabMV does not act as an antagonist against PRSV in C. papaya. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.